2017
DOI: 10.1111/acel.12648
|View full text |Cite
|
Sign up to set email alerts
|

Dyrk1 inhibition improves Alzheimer's disease‐like pathology

Abstract: SummaryThere is an urgent need for the development of new therapeutic strategies for Alzheimer's disease (AD). The dual‐specificity tyrosine phosphorylation‐regulated kinase‐1A (Dyrk1a) is a protein kinase that phosphorylates the amyloid precursor protein (APP) and tau and thus represents a link between two key proteins involved in AD pathogenesis. Furthermore, Dyrk1a is upregulated in postmortem human brains, and high levels of Dyrk1a are associated with mental retardation. Here, we sought to determine the ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
80
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 102 publications
(82 citation statements)
references
References 35 publications
2
80
0
Order By: Relevance
“…Finally, while the apparent complementary actions of DYRK1A inhibitors and TGFb superfamily inhibitors, illustrated in Figure 7A, likely explain much of the apparent synergy, they are unlikely the exclusive mechanism for the observed synergy, as evidenced by the ability of harmine alone to modulate expression and abundance of TGFb superfamily members ( Figure 3A; Table S2). Indeed, several reports indicate that DYRK1A can phosphorylate a broad range of targets in addition to the NFaT family, including Tau, TP53, p27 CIP , and the DREAM complex member LIN52 (Abdolazimi et al, 2018;Branca et al, 2017;Litovchick et al, 2011;Park et al, 2010;Sadasivam and DeCaprio, 2013). We thus speculate that currently unknown additional targets likely exist that may lead to destabilization and/or dephosphorylation of SMADs as observed in Figure 3A.…”
Section: Discussionmentioning
confidence: 72%
“…Finally, while the apparent complementary actions of DYRK1A inhibitors and TGFb superfamily inhibitors, illustrated in Figure 7A, likely explain much of the apparent synergy, they are unlikely the exclusive mechanism for the observed synergy, as evidenced by the ability of harmine alone to modulate expression and abundance of TGFb superfamily members ( Figure 3A; Table S2). Indeed, several reports indicate that DYRK1A can phosphorylate a broad range of targets in addition to the NFaT family, including Tau, TP53, p27 CIP , and the DREAM complex member LIN52 (Abdolazimi et al, 2018;Branca et al, 2017;Litovchick et al, 2011;Park et al, 2010;Sadasivam and DeCaprio, 2013). We thus speculate that currently unknown additional targets likely exist that may lead to destabilization and/or dephosphorylation of SMADs as observed in Figure 3A.…”
Section: Discussionmentioning
confidence: 72%
“…In the first decade of life, a time when there is little amyloid deposition [34,35], plasma Aβ42 levels were on average a little higher (~1.6 fold) in DS than the expected 1.5-fold elevation due to gene dosage. Why this should be is unclear, but it is worth noting that several AD risk factors are encoded on chromosome 21 [2] and these might contribute to either enhanced amyloidogenic processing of APP [36,37] or reduced degradation of Aβ [38]. Also, neuronal Aβ production is activity dependent [39] and in DS there is evidence of aberrant hyperactivity during development and early life [40] that could contribute to higher Aβ levels.…”
Section: Discussionmentioning
confidence: 99%
“…Inhibition of DYRK1A may reduce these factors and the pathogenesis of AD. Proof‐of‐concept studies with DYRK1A inhibitors have demonstrated a reduction in amyloid pathology, insoluble tau phosphorylation, and neuroprotection in mice (Branca et al, ; Naert et al, ; Neumann et al, ). Previous attempts at modulating kinases in patients (GSK‐3β) may have failed due to the low potency and limited bioavailability of those compounds.…”
Section: Discussionmentioning
confidence: 99%